Dominant Activity of Activation Function 1 (AF-1) and Differential Stoichiometric Requirements for AF-1 and -2 in the Estrogen Receptor α-β Heterodimeric Complex - Tremblay, Gilles B. (American Society for Microbiology, 1999)
Estrogenic responses are now known to be mediated by two forms of estrogen receptors (ER), ERα and ERβ, that can function as homodimers or heterodimers. As homodimers the two have been recently shown to exhibit distinct transcriptional responses to estradiol (E(2)), antiestrogens, and coactivators, suggesting that the ER complexes are not functionally equivalent. However, because the three possible configurations of ER complexes all recognize the same estrogen response element, it has not been possible to evaluate the transcriptional properties of the ER heterodimer complex by transfection assays. Using ER subunits with modified DNA recognition specificity, we were able to measure the transcriptional properties of ERα-ERβ heterodimers in transfected cells without interference from the two ER homodimer complexes. We first demonstrated that the individual activation function 1 (AF-1) domains act in a dominant manner within the ERα-ERβ heterodimer: the mixed agonist-antagonist 4-hydroxytamoxifen acts as an agonist in a promoter- and cell context-dependent manner via the ERα AF-1, while activation of the complex by the mitogen-activated protein kinase (MAPK) pathway requires only the ERα- or ERβ-responsive MAPK site. Using ligand-binding and AF-2-defective mutants, we further demonstrated that while the ERα-ERβ heterodimer can be activated when only one E(2)-binding competent partner is present per dimer, two functional AF-2 domains are required for transcriptional activity. Taken together, the results of this study of a retinoid X receptor-independent heterodimer complex, the first such study, provide evidence of different stoichiometric requirements for AF-1 and -2 activity and demonstrate that AF-1 receptor-specific properties are maintained within the ERα-ERβ heterodimer.